Role of Threat and Coping Appraisal in Protection Motivation for Adoption of Preventive Behavior During COVID-19 Pandemic - Lahiri, Arista; Jha, Sweety Suman; Chakraborty, Arup; Dobe, Madhumita; Dey, Abhijit (Frontiers in Public Health, 2021)
With more than 100 million cases and over 2 million deaths globally, the COVID-19 pandemic continues to remain a major threat. Identifying the behavioral factors influencing preventive behaviors for COVID-19 are crucial in devising public health policies to promote essential strategies to combat the pandemic in an efficient manner. The current study was therefore conducted to estimate the prevalence of COVID-19 preventive behaviors and measure their association with behavioral constructs like threat perception, response efficacy, and self-efficacy, as per socio-demographic background. A region-stratified online survey focusing on the constructs of protection motivation theory, for example, threat and coping appraisal for preventive health practices against COVID-19, was carried out among adult users of social media in India. Generalized linear models with cluster-adjusted-robust standard errors were used to analyze the responses and model the preventive practices among the study population. Analysis of a total 2,646 responses revealed that proper perceptions regarding cause, symptoms, and transmission of COVID-19 were prevalent in the majority of the respondents. The majority of the participants reported frequent use of face masks (93.20%), followed by frequent washing of hands with soap and water (84.90%). The majority of the respondents affirmed that, though not frequently but sometimes, they avoid touching the face with unclean hands. Frequently covering mouth with the crook of the elbow while sneezing and coughing, and maintaining physical distance when outside was noted among 74.14 and 83.84%, respectively. The proportion of participants frequently using sanitizers to clean hands and those infrequently practicing the same were comparable. Self-efficacy for preventive practices and threat-appraisal of COVID-19 illness were identified as important determinants of the selected COVID-19 preventive behaviors, independently. The analysis confirmed that practices of the behaviors were mostly synergistic to each other. Current findings highlight that formulation of precise risk communication strategies to improve perceptions regarding threat appraisal and self-efficacy could facilitate desirable practices, which are also effective in the prevention of airborne infections and, hence, may contribute toward broader policy directions. The evidence urges the implementation of precision-driven risk communication and diffusion of these practices to attain behavioral herd immunity.